Vortex assisted liquid-liquid microextraction with back extraction of repaglinide, glibenclamide and glimepiride in water samples - Sohaib Jumaah Owaid Luhaib; Noorfatimah Yahaya; Alshishani, Anas; Maizatul Najwa Jajuli; Mazidatulakmam Miskam (Penerbit Universiti Kebangsaan Malaysia, 2021)
A new analytical method based on vortex-assisted liquid-liquid microextraction with back extraction (VALLME-BE) coupled with high performance liquid chromatography was developed for the simultaneous determination of antidiabetic drugs; repaglinide, glibenclamide, and glimepiride in water samples. Chromatographic separation was achieved using C18 column (250 × 4.6 mm × 5 µm) and methanol-phosphate buffer (pH3.7) in the ratio of 70:30 v/v as a mobile phase at a flow rate of 1 mLmin-1. VALLME-BE was performed using 200 μL of n-octane dispersed into the aqueous sample (10 mL) with the aid of vortexing agitation. Then, the analytes were back-extracted from the organic solvent to 0.05 M NaOH (40 µL). Under these conditions, enrichment factor of 155-fold was achieved. The developed VALLME-BE method showed excellent linearity in the range of 30 to 1000 µgL-1 with limit of detection (LOD) of 0.41-1.66 µgL-1 and limit of quantification (LOQ) of 1.38-5.54. 41-1.66 µgL-1. VALLME-BE was applied for the determination of repaglinide, glibenclamide and glimepiride in water samples with the recoveries ranged from 83-109%. The relative standard deviation for inter-day and intra-day precision was less than 9.9%.